2007
DOI: 10.3171/jns.2007.106.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a novel polyethylene glycol hydrogel sealant for watertight dural repair

Abstract: The PEG hydrogel sealant provides a safe and effective watertight closure when used as an adjunct to sutured dural repair during cranial surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
110
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 35 publications
(27 reference statements)
1
110
0
2
Order By: Relevance
“…Boogarts et al [2] reported no evidence of postapplication cerebrospinal fluid leaks or adverse events in 46 patients who had a spontaneous dural tear treated with DuraSeal TM . Cosgrove et al [5] reported similar findings with no evidence of postapplication cerebrospinal fluid leaks in 95.5% of patients and no adverse events with the use of DuraSeal TM . After these reports, the use of DuraSeal TM was extended as an adjunct to suture closure of an iatrogenic dural tear.…”
Section: Discussionsupporting
confidence: 63%
“…Boogarts et al [2] reported no evidence of postapplication cerebrospinal fluid leaks or adverse events in 46 patients who had a spontaneous dural tear treated with DuraSeal TM . Cosgrove et al [5] reported similar findings with no evidence of postapplication cerebrospinal fluid leaks in 95.5% of patients and no adverse events with the use of DuraSeal TM . After these reports, the use of DuraSeal TM was extended as an adjunct to suture closure of an iatrogenic dural tear.…”
Section: Discussionsupporting
confidence: 63%
“…15 Dural sealants have been described to be safe when used in combination with autologous dural substitute material. 8,19,35 However, there is no consensus on a standardization of dural closure, and only a few clinical studies assessed outcomes of various closure methods in a randomized and controlled manner. Kim and Wright 19 and Osbun et al 25 prospectively assessed the addition of polyethylene glycol hydrogel sealant (DuraSeal, Covidien) in spinal and cranial surgery for dural closure in comparison with standard techniques that included various dural augmentation methods according to the surgeon's choice.…”
mentioning
confidence: 99%
“…2,3,[14][15][16] This hydrogel sealant system can also be used to seal dural defects. Polyethylene glycol hydrogel sealant is a chemical synthetic sealant formed by mixing PEG ester solution and trilysine amine solution.…”
mentioning
confidence: 99%